The Efficiency of Bookkeeping Financial Transactions in The Preparation of Financial Reports the Ward Financial Institution Patihan Manguharjo District Madiun City - Rino Wiwoho (Politeknik Negeri Madiun, 2023)
At the end of each quarter and at the end of each year The Ward Financial Institution (TWFI) Patihan is obliged to submit financial reports to the Madiun City Government through the relevant offices. Financial reports are submitted in printed form. Making TWFI financial reports is seen as inefficient. Recording of financial transactions still uses a single-entry system. Some financial records that are not really needed must still be attached to the financial statements. The system for recording financial transactions that is deemed necessary to be implemented at TWFI Patihan is a double entry system. In this study, the Microsoft Office Excel application was used. All the required accounts are poured into sheets, one account per sheet, like a ledger. Each account displays its balance. Each balance of the account is linked to balance sheet, Income Statement, statement of equity and Cash Flow. Every time there is a new transaction and it has been recorded in both debit and credit accounts, the value of the account in the financial statements will also change. The results of the study show that recording financial transactions with a double entry system is more appropriate for TWFI. Reporting to the Madiun City Government can be submitted in one file which includes all accounts with their balances and the required financial statements. TWFI management needs to improve skills in recording every transaction with a double entry system.